Transport Phenomena Fundamentals - Plawsky, Joel L. (Chemical industries, 2019)
The fourth edition of Transport Phenomena Fundamentals continues with its streamlined approach to the subject, based on a unified treatment of heat, mass, and momentum transport using a balance equation approach. The new edition includes more worked examples within each chapter and adds confidence-building problems at the end of each chapter. Some numerical solutions are included in an appendix for students to check their comprehension of key concepts. Additional resources online include exercises that can be practiced using a wide range of software programs available for simulating engineering problems, such as, COMSOL®, Maple®, Fluent, Aspen, Mathematica, Python and MATLAB®, lecture notes, and past exams. This edition incorporates a wider range of problems to expand the utility of the text beyond chemical engineering.